Ein Beitrag zur viskoelastischen Modellierung nichtholonomer Bindungsgleichungen - Deppler, Jens (KIT Scientific Publishing, 2017)
Based on a formalism to simulate mechanical rigid body systems with plane frictional contacts, an extension to systems with rolling contacts is proposed. A special focus is put on tagential contact compliance. A mathematical convergency proof of the solution of the tangential elastic formulation to the rigid one is proposed.
German
Keywords: Kontaktmechaniknonholonomic; Mehrkörperdynamik; regularization; nichtholonom; multibody systems; Zwangsbedingung; contact mechanics; Regularisierung; constraints